Side chain packing states of chitosan‐based supramolecular derivatives containing long alkyl side chains. Issue 2 (18th March 2020) - Liu, Lingzhi; Lyu, Dong; Xiang, Mingyue; Men, Yongfeng
Abstract: A series of chitosan‐based supramolecular comb‐like polymers containing long alkyl side chain were prepared. They aggregated into layered structure. When the alkyl side chain was longer than 16 carbons, the long alkyl side chains exhibited crystallization behavior. During heating process, the packing structure of comb‐like polymers with side chain length from 10 to 20 showed a peculiar behavior of volume shrinkage, but that of samples with much longer side chain (>22) expanded. Such results could be attributed to the different packing structure of side chains when they possess different length. Both the steric hindrance and the tendency of side chain aggregation affect the packing state of alkyl side chains together. Abstract : A series of chitosan‐based supramolecular comb‐like polymers containing long alkyl side chains were prepared via non‐covalent bonds. All these comb‐like polymers aggregate into a layered structure. The side‐chain packing structure of these comb‐like polymers depends on the side chain length. Both the steric hindrance and the tendency of side‐chain aggregation affect the packing state of alkyl side chains together.